Learning to Lead: Lessons From the Field (LEARNing Landscapes, 2008)
In this article, the author recalls experiences from her career, and shares them as five lessons learned about leadership. She explains that a mentoring culture did not exist for her or others when she assumed various leadership roles in her school board, and she argues that possibilities exist for a strong mentoring culture now. The five lessons presented focus on caring and compassion, trust and risk-taking, listening, collaboration and shared governance, and facilitating and mentoring.
Keywords: leadership; mentoring; care; trust; rsik-taking; listening; collaboration; shared governance; facilitation